Detection transposable elements in Botrytis cinerea in latent infection stage from symptomless apples - Fernández, Jorge Gastón (2014)
Detection of Botrytis cinerea latent infections on apples before storage is essential for effective control strategies in the fruit postharvest industry. In the present study a PCR detection method, based on primers designed on B. cinerea transposable elements (boty and flipper) and intergenic spacer (IGS) region as internal control were utilized to reveal the presence of symptomless infections on apple fruits. The method molecular proved to be highly specific and sensitive in detecting latent infections, revealed the presence of the pathogen in 83% of the samples from infected apples with 104 conidia/mL, whereas those infected with 106 conidia/mL detected 94% as compared to the traditional method that revealed the pathogen in 40 and 66% of the samples inoculated with 104 and 106 conidia/mL respectively. Furthermore, the method characterized B. cinerea as subpopulation transposa-type by the presence of the transposable elements boty and flipper The results obtained of DNA quantification method were compared with ELISA assay and these studies showed good correlation. Therefore our method has important advantages compared with others detection methods for B. cinerea, because the proposed methodology allowed distinguishes between its two subpopulations (vacuma and transposa) and this would allow establish possible control appropriate strategies. Finally, the method can be an interesting alternative for its possible application in the phytosanitary programs of the fruit industry worldwide.